Business management and communication perspectives in industry 4.0 - Tunc, Aysegul Ozbebek, 1985-; Aslan, Pinar (Advances in logistics, operations, and management science (ALOMS) book series., 2020)
"This book examines issues in business management, leadership, strategic communication, social media, crisis management, organization structure, business models, robotics, and digital strategies in relation to Industry 4.0"--